2022
DOI: 10.1128/spectrum.01587-22
|View full text |Cite
|
Sign up to set email alerts
|

Arbovirus Screening in Mosquitoes in Emilia-Romagna (Italy, 2021) and Isolation of Tahyna Virus

Abstract: We reported in this work the detection of three Arboviruses (Arthropod-borne viruses) in mosquitoes collected in Emilia-Romagna in 2021. In addition to West Nile and Usutu viruses, which were reported from more than 10 years in the study area, we detected and isolated Tahyna virus (TAHV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Although prior experiments were unable to establish that An. maculipennis were capable of being infected, recent evidence suggests that these mosquitoes are also exposed to TAHV in Italy (Calzolari et al, 2022). Outside mosquitoes, two isolations of TAHV have come from biting midges Culicoides in the Bohemian-Moravian highlands (Českomoravská vysočina).…”
Section: Mosqu Ito Vec Tor Smentioning
confidence: 99%
See 2 more Smart Citations
“…Although prior experiments were unable to establish that An. maculipennis were capable of being infected, recent evidence suggests that these mosquitoes are also exposed to TAHV in Italy (Calzolari et al, 2022). Outside mosquitoes, two isolations of TAHV have come from biting midges Culicoides in the Bohemian-Moravian highlands (Českomoravská vysočina).…”
Section: Mosqu Ito Vec Tor Smentioning
confidence: 99%
“…During these outbreaks, serological results showed that exposure to TAHV was higher in flooded and adjacent regions of large rivers, such as the Vltava, Thaya (Dyja) and Elbe, where massive populations of floodplain mosquitoes occur. The virus has been detected in various ecosystems, including the southern taiga, deciduous forests, steppes and semi‐arid zones in the central and southern areas of the Russian Plain, as well as in the Pannonian plains, and in the marshland plains of the Po river basin in Italy (Aspöck & Kunz, 1971; Calzolari et al, 2022; Camp et al, 2021; L'vov et al, 1987). Serological evidence suggests that TAHV activity also extends along the Danube River, from Austria to the delta in Romania (Arcan et al, 1974; Camp et al, 2018).…”
Section: Natural Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…caspius pool collected in the municipality of Comacchio. Furthermore, TAHV was detected in 10 mosquito pools sampled in 2009, 2010, and 2020, confirming the continuous presence of the virus in this region [ 22 ]. In the present study, all tested Ae.…”
Section: Discussionmentioning
confidence: 86%
“…West Nile virus (WNV) is a mosquito-borne RNA virus (genus Flavivirus, family Flaviviridae) that, since 1962 and similarly to other arboviruses (e.g., tick-borne encephalitis virus or TBEV) [1,2], has progressively become endemic in large areas of continental Europe [3][4][5][6][7][8], where it is mainly carried by endogenous mosquito species of the genus Culex (C. pipiens, C. peregrinus, and C. modestus) [7,9,10], with a more limited role for Aedes spp. [11][12][13]. Arthropod vectors then sustain the enzootic "amplification" cycle within the main hosts, migratory birds [5][6][7]9,14].…”
Section: Introductionmentioning
confidence: 99%